Magnetic Field Induced Changes in the Shoot and Root Proteome of Barley (Hordeum vulgare L.) - Shabrangy, Azita; Ghatak, Arindam; Zhang, Shuang; Priller, Alfred; Chaturvedi, Palak; Weckwerth, Wolfram (Frontiers in Plant Science, 2021)
Geomagnetic field (GMF) has been present since the beginning of plant evolution. Recently, some researchers have focused their efforts on employing magnetic fields (MFs) higher than GMF to improve the seed germination, growth and harvest of agriculturally important crop plants, as MFs are inexpensive and environment-friendly technique. In this study, we have employed different treatments considering MF of 7 mT (milliTesla) at the different time point of the exposure including 1, 3, and 6 h as treatment, following most extended exposure for five consecutive days, 6h per day in barely seeds. The results showed a positive impact of MF on growth characteristics for five-day-old seedlings, including seed germination rate, root and shoot length and biomass weight; however, significant effects were observed in long exposure. Furthermore, ~5 days’ delay of flowering in pre-treated plants was also observed. We have used a shotgun proteomics approach to identify changes in the protein signatures of root and shoot tissues under MF effects. In total, we have identified 2896 proteins. Thirty-eight proteins in shoot and 15 proteins in root showed significant changes under the MF effect. Proteins involved in primary metabolic pathways were increased in contrast to the proteins with metal ion binding function, proteins contain iron ion in their structure and proteins involved in electron transfer chain were decreased significantly in the treated tissues. The upregulated proteins' overall biological processes were carbohydrate metabolic process, oxidation-reduction process, and cell redox homeostasis, while down-regulated processes include translation and protein refolding. In general, shoot response was more affected to MF effect than root tissue leading to the identification of 41 shoot specific proteins. This study provides a first insight into the proteome regulation response to MF during the barley's seedling stage.